2014
DOI: 10.3390/ijms15022305
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in the Endoplasmic Reticulum N-Glycosylation Pathway of the Red Microalga Porphyridium sp.: A Bioinformatic Study

Abstract: N-glycosylation is one of the most important post-translational modifications that influence protein polymorphism, including protein structures and their functions. Although this important biological process has been extensively studied in mammals, only limited knowledge exists regarding glycosylation in algae. The current research is focused on the red microalga Porphyridium sp., which is a potentially valuable source for various applications, such as skin therapy, food, and pharmaceuticals. The enzymes invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 88 publications
2
31
0
Order By: Relevance
“…Bioinformatic studies using our in‐house c‐DNA genome (Levy‐Ontman et al. ) indicated that the algal GANAB glycoenzyme is a dimer of α (125 kDa) and β subunit (58 kDa), sharing homology to other ortholog enzymes derived from a range lower to more complex eukaryotes. Indeed, the high similarity of the algal glycoenzyme to its orthologs suggests that these exo‐type glycosidases that act with a retention mechanism (releasing α‐D‐glucopyranose with retention of the configuration in the anomeric position; Chiba ) are conserved across evolution eras and its importance is highlighted in eukaryotes in general and photosynthetic organisms in particular.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bioinformatic studies using our in‐house c‐DNA genome (Levy‐Ontman et al. ) indicated that the algal GANAB glycoenzyme is a dimer of α (125 kDa) and β subunit (58 kDa), sharing homology to other ortholog enzymes derived from a range lower to more complex eukaryotes. Indeed, the high similarity of the algal glycoenzyme to its orthologs suggests that these exo‐type glycosidases that act with a retention mechanism (releasing α‐D‐glucopyranose with retention of the configuration in the anomeric position; Chiba ) are conserved across evolution eras and its importance is highlighted in eukaryotes in general and photosynthetic organisms in particular.…”
Section: Discussionmentioning
confidence: 99%
“…) and by identifying the encoded genes related to the ER N‐glycosylation pathway (Levy‐Ontman et al. ). It appears that the ER N‐glycosylation pathway in Porphyridium sp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Asn-X-(Ser/thr), however, the precise regulation process implicated in the N-glycosylation is still unknown [45,46]. It has been suggested that the N-glycosylation concerns only the accessible asparagine.…”
Section: Seeking For a Sequence Common To The Csl Ligandsmentioning
confidence: 99%